Environmental Visual Concept of Hybrid Animated Film ‘Si Dulang’ For Fine Dining Projection Mapping - Rahmi, Dila Febriyana; Lukmanto, Christine Mersiana; Rahmiaty, Siti Adlina (VCD: Journal of Visual Communication Design, 2024)
Technology and animation are the combinations that complete each other. It would be interesting to see how culinary cuisine comes into play in between. The research journey on how to enhance the immersive experience in fine dining with a projection mapping on a table by using a video projector to map hybrid animation has broadened the cutting-edge digital art and industrial area. In creating an immersive environment that complements Indonesian food and is tailored to the themes, ideas, and concepts, this research objective is focused on the environmental visualization concept of an animated film called ‘Si Dulang’, which is heavily impacted by Bali cultural aspects and based on famous attractions in Bali. Literature studies and observations of various projection mappings will be used as a research method to achieve a prototype of the animated film and environmental visual concept. The result is following the concept designed from the beginning although there are improvements in the composition arrangement. Therefore, it takes several tries to find the appropriate size of the object projected from the projector.